A newly recognized species in the Anopheles Hyrcanus Group and molecular identification of related species from the Republic of South Korea (Diptera: Culicidae) - Li, Cong; Lee, John S.; Groebner, Jennifer L.; Kim, Hueng-Chul; Klein, Terry A.; O’guinn, Monica L.; Wilkerson, Richard C. (Zootaxa, 2005)
We report here a previously unrecognized mosquito species from the Republic of South Korea that is closely related to Anopheles (Anopheles) sinensis. We also present an rDNA ITS2-based method for identification of this and the other morphologically similar Anopheles from the country. The PCR assay is a multiplex of seven primers in a single reaction that unambiguously identifies all included species. The other species include An. sinensis, An. lesteri, An. pullus, and a previously reported unknown Anopheles. Based on the ITS2 sequence, the two unnamed species have genetic distances from An. sinensis of 9.1% (unknown 1) and 10.7% (unknown 2), and are 10.6% different from each other. Adult females of An. sinensis and unknown 2 are morphologically indistinguishable, while unknown 1, An. lesteri and An. pullus can usually be separated from each other and from An. sinensis using available keys and descriptions. This PCR identification tool offers vector biologists and malaria epidemiologists a means to identify the potential vectors of malaria parasites in South Korea.